PEMIKIRAN FILOSOFIS SADRA DALAM TAFSĪR AL-QUR’ĀN AL- KARĪM : : SURAH AL-’A‘LĀ - Kerwanto (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2014)
In his commentary on Surah al-’ A‘lā, Mulla Sadra, through his Tafsīr al-Qur’ān al-Karīm invites our souls to ventureinto the deepest layers of meaning to recognize the reality of Divinity (almabdā’), prophethood (Ṣirāṭ or nubuwwah) and resurrection (ma‘ād) and discusses it in a more philosophical manner. This study is an attempt to explore the benefits of these important aspects of religious sources unearthed from Qur’anic injunctions combined with rational principles of philosophical and mystical experiences (intuitive) of Sadra. Each chapter in this commentary is assigned a title with tasbīḥ (glorification), while presenting various issues related to metaphysics of Qur’an.Thephilosophical principles used in the interpretation of this treatise could be a proof of harmony between philosophy and religious texts. This kind of interpretation accepts the literal meaning (ẓāhir) of lafaẓ al Qur’ān, and then with the aid of reason, intuition and revelation uncover the reality behind them; the search for the secrets behind the literal sense.